Endoplasmic reticulum stress caused by traumatic injury promotes cardiomyocyte apoptosis through acetylation modification of GRP78 - Yan Zi; Liu Yufeng; Yang Bowen; Zhao Wenhui; Wang Yan; Wang Deping; Li Jianguo; Jiao Xiangying; Cao Jimin (Acta Biochimica et Biophysica Sinica, 2023)
Cardiomyocyte apoptosis is an important cause of trauma-induced secondary cardiac injury (TISCI), in which the endoplasmic reticulum stress (ERS)-mediated apoptosis signaling pathway is known to be first activated, but the mechanism remains unclear. In this study, rat models of traumatic injury are established by using the Noble-Collip trauma device. The expression of glucose-regulating protein 78 (GRP78, a molecular chaperone of the cardiomyocyte ER), acetylation modification of GRP78 and apoptosis of cardiomyocytes are determined. The results show that ERS-induced GRP78 elevation does not induce cardiomyocyte apoptosis in the early stage of trauma. However, with prolonged ERS, the GRP78 acetylation level is elevated, and the apoptosis of cardiomyocytes also increases significantly. In addition, in the early stage of trauma, the expression of histone acetyl-transferase (HAT) P300 is increased and that of histone deacetylase 6 (HDAC6) is decreased in cardiomyocytes. Inhibition of HDAC function could induce the apoptosis of traumatic cardiomyocytes by increasing the acetylation level of GRP78. Our present study demonstrates for the first time that post-traumatic protracted ERS can promote cardiomyocyte apoptosis by increasing the acetylation level of GRP78, which may provide an experimental basis for seeking early molecular events of TISCI.